Analisa Pelanggaran Etika Profesi Akuntansi Studi Kasus PT Hanson Internasional Tbk (MYRX) - Saridawati Saridawati; Okky Kharisma; Olivia Purama J; Valencya Valencya; Viera Pramestya (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the violation of professional accounting ethics in the case of PT Hanson International Tbk (MYRX), a public company involved in financial statement manipulation and bond default. The research adopts a qualitative approach using a case study method, based on secondary data from financial reports, media coverage, and official documents from financial authorities. The findings indicate serious breaches of ethical principles in the accounting profession, including integrity, objectivity, and professional competence. These violations had significant impacts on investor trust, capital market stability, and the reputation of the accounting profession. Moreover, the case highlights the urgent need for stronger supervision, reforms in financial reporting practices, and the integration of ethical values in accounting activities. This study contributes to a deeper understanding of the importance of ethics in maintaining transparency and accountability in financial reporting.